Complaint Management Strategy in Dealing with Allegations of Malpractice in the Digital Age - Rosliana Mahardhika; Edi Sumarwanto; Elsye Maria Rosa (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
According to the data from Central Indonesian Doctors Association (IDI) Legal Aid Institute, in Indonesia there are approximately 210 cases of suspected malpractice. Medical accidents have caused real injury to the patients, health care system, and reduced trust between the patients and medical personnel. This study aims to identify the hospital strategies in dealing with patient complaints due to alleged malpractice in digital era. This study conducted the preparation of literature review with systematic technique in selecting and searching using international and national databases. Due to large number of complaints that come in, it is important for hospitals to create a complaint handling system by improving the complaint handling process by preparing professional resources in handling the complaints. The preventive efforts are also needed by increasing awareness about patient safety, implemented the service procedures in accordance with existing SOPs, and filling out the documents properly and correctly such as requesting a letter of approval for action by providing an explanation of procedures and prognosis of treatment.